Peningkatan Kapasitas UMKM Keripik di Desa Tunggulsari melalui Pemberdayaan Pencatatan Keuangan - Sari Rahmadhani; Kiswoyo Kiswoyo; Tarisya Adeloktary; Jumari Al Ihsan (CV. ALIM'SPUBLISHING, 2025)
This community service activity aims to improve the financial management ability of Micro, Small, and Medium Enterprises (MSMEs) chips in Tunggulsari Village, Brangsong District, Kendal, Central Java. Given the limited access to technology, the mentoring approach is carried out flexibly, combining manual and digital methods. Training focuses on using notebooks, simple tables, and calculators. For MSMEs that have access to smartphones, training is given on using simple financial recording applications. The activity results showed a significant improvement in the ability of MSMEs to record transactions and understand simple financial statements. Despite the obstacles to access to technology, this activity has succeeded in increasing financial capacity with an adaptive approach. Thus, it is hoped that MSMEs in Tunggulsari Village can make better business decisions and improve the competitiveness of MSME chips.